The Efficiency Implications of Earnings Retentions - McFetridge, Donald G. (The Review of Economics and Statistics, 1978)
Implicit here is the argument that the owners of the corporation and hence the economy as a whole gain from allowing management to reinvest past profits on their behalf. This must be, true if it is assumed that managers always act in the interest of the owners. If, however, managers act in their own interest, their retention and reinvestment of past profits can be a source of inefficiency. Mueller (1969) has observed that, although the investment opportunities of the stockholders may be better than those which management can internalize,